Effects of amyloid precursor protein and environmental enrichment on plasticity and neuroprotection: a review focusing on aging and Alzheimer’s disease - Neves, Rodrigo Colaço das (2025)
Amyloid Precursor Amyloid (APP) is a transmembrane glycoprotein which shows several functions during plastic processes and on nervous system development. These functions are mainly performed by its metabolites after APP proteolytic process, that can occur in two distinct pathways. On non-amyloidogenic pathway APP is cleavage by α-secretase and releases sAPPα, which has functions on development and plasticity. On amyloidogenic pathway APP is cleavage by β-secretase and releases sAPPβ and Aβ peptide, which can aggregate in oligomers when overproduced, inducing synaptic decline and cellular death, and senile plaques, histopathologic hallmarks of Alzheimer’s Disease (AD). Environmental Enrichment (EE) is change on housing pattern which promotes an increase on cognitive stimulus and studies have been demonstrated that EE has a potential role on plasticity in several conditions and experimental models. Aiming reunite new studies on literature related to APP, EE and plasticity, the present systematic review used PubMed and ScienceDirect and 85 works were used. The selected articles suggested that APP has important functions to plasticity when induced and reinforced LTP and attenuated disturbed behaviors on knockout models. sAPPα seems to exercise significative plastic functions, being able to rescue LTP and increase the expression of proteins associated to plastic phenomena. It was also seen that these functions can be related to the structure and amino acids sequency found on sAPPα. Furthermore, sAPPα showed neuroprotective functions on injury models and mainly on AD model. The EE also showed itself as a good plasticity inductor when enhanced LTP and behavior in animals under different conditions, such as AD model. About the mechanisms, it was evidenced a relation with glutamatergic system through modulation of proteins associated with signaling mediated by glutamate. Moreover, many studies demonstrated an upregulation of BDNF and synaptic proteins as SYN and PSD95. These data also suggest an EE’s neuroprotective function in the context of aging and AD. Therefore, sAPPα and EE can be targets on therapeutic approaches which seek induce neurogenesis and plasticity.